Large thermoelectric power factor in whisker crystals of solid solutions of the one-dimensional tellurides Ta4SiTe4 and Nb4SiTe4. (3rd December 2020) - Yoshikawa, Yuma; Wada, Taichi; Okamoto, Yoshihiko; Abe, Yasuhiro; Takenaka, Koshi
Abstract: One-dimensional tellurides Ta4 SiTe4 and Nb4 SiTe4 were found to show high thermoelectric performance below room temperature. This study reported the synthesis and thermoelectric properties of Ta4 SiTe4 -Nb4 SiTe4 solid solutions and Mo- or Ti-doped (Ta0.5 Nb0.5 )4 SiTe4 . Thermoelectric power of the solid solutions systematically increased with increasing Ta content, while their electrical resistivity was unexpectedly small. Mo- and Ti-doped (Ta0.5 Nb0.5 )4 SiTe4 showed n- and p-type thermoelectric properties with large power factors exceeding 40 μ W cm −1 K −2, respectively. The fact that not only Ta4 SiTe4 and Nb4 SiTe4 but also their solid solutions showed high performance indicated that this system is a promising candidate for thermoelectric applications at low temperatures.